P085 MEP variability associated with coil pitch and roll using single-pulse TMS. Issue 3 (March 2017) - Grey, M.; van de Ruit, M.
Abstract : The motor evoked potential (MEP) elicited by transcranial magnetic stimulation (TMS) applied over the motor cortex is well-known to have considerable variability. The use of navigated brain stimulation has been commonly employed to reduce error induced by coil movement under the assumption that maintaining tighter control over coil position and orientation will reduce trial-to-trial variability. A few studies have investigated the yaw orientation which produces the largest MEP and it is common to choose the yaw angle based on the specific area of the motor cortex being stimulated (e.g. 45° to the sagittal plane for the hand area, inline with the sagittal plane for the foot and leg). The objective of the present study was to assess the effect of coil tilt about the roll and pitch axes in order to determine how quickly the MEP drops off from its maximum. 26 participants were recruited to the study. MEPs were recorded from the First Dorsal Interosseous (FDI) muscle of the right hand in response to magnetic stimuli delivered at 120% resting motor threshold. Stimulation was delivered with a Magstim Rapid 2 biphasic stimulator. Coil position and orientation were recorded for each MEP using the frameless stereotaxy (Brainsight 2, Rogue Research). 25 MEPs were recorded in 3° increments over a range of 60° around the pitch and roll axes. As expected MEPs decreased as the coil was rotated about either the pitch or roll aces. Across all participants, MEPs were reduced to 70% of their maximum value when the coil was rotated by 30 ± 10° about the roll axis and by 17 ± 4° about the pitch axis. The results of this study suggest significantly more sensitivity to rotation about the roll axis compared with the pitch axis (p < 0.05). However, the data also suggest that MEPs are relatively insensitive to small rotations about these axes.